High-wear-resistance piston rod based on gas spring and preparation method of high-wear-resistance piston rod
By using laser cladding process on the surface of the piston rod to form an iron-based alloy cladding layer and applying a specific wear-resistant coating, the problem of insufficient wear resistance of the conventional piston rod is solved, and the wear resistance and service life of the piston rod is significantly improved.
Patent Information
- Application Number
- CN202510154367.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-12
AI Technical Summary
Traditional piston rods are prone to deterioration in long-term reciprocating motion due to friction and wear, and traditional surface treatment technology is difficult to meet the requirements of high wear resistance, and there are environmental pollution problems.
A laser cladding process is used to form an iron-based alloy cladding layer on the surface of the piston rod, and an wear-resistant coating composed of epoxy resin, aminated molybdenum disulfide and aminated silicon carbide are coated on the cladding layer to form an wear-resistant coating.
It significantly improves the wear resistance and service life of the piston rod, enhances the surface hardness and wear resistance of the coating, reduces wear and effectively prevents wear in high friction environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piston rods, and in particular to a high-wear-resistant piston rod based on a gas spring and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry, especially in the fields of automobiles, engineering machinery, aerospace, etc., gas springs, as an important elastic element, are increasingly used. The performance of gas springs directly affects the stability and service life of the entire mechanical system. As one of the core components of gas springs, the piston rod is particularly important for its wear resistance, strength and toughness.
[0003] Traditional piston rods are mostly made of ordinary steel. Although they have certain strength and rigidity, they are prone to performance degradation or even breakage due to friction and wear during long-term reciprocating motion. In addition, the surface treatment technology of traditional piston rods is limited and it is difficult to meet the requirements of high wear resistance. At present, the surface treatment of piston rods in my country mainly relies on the traditional electroplating chrome process. However, this technology will cause serious environmental pollution during production and use.
[0004] Therefore, we propose a high wear-resistant piston rod based on a gas spring and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a highly wear-resistant piston rod based on a gas spring and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a highly wear-resistant piston rod based on a gas spring comprises the following steps:
[0008] Step S1: Degreasing, cleaning and drying the piston rod to obtain a pre-treated piston rod;
[0009] Step S2: cladding the cladding powder onto the surface of the pretreated piston rod through a laser cladding process to form a cladding layer;
[0010] Step S3: mixing epoxy resin and xylene evenly, adding the composite, curing agent, leveling agent and defoaming agent and mixing evenly to obtain a wear-resistant coating;
[0011] Step S4: coating the surface of the cladding layer with a wear-resistant coating, and after drying and curing, forming a wear-resistant coating to obtain a highly wear-resistant piston rod.
[0012] Furthermore, the cladding powder is iron-based alloy powder.
[0013] Furthermore, in step S2, the laser cladding process conditions are: laser power 3500-4500 W, cladding speed 10-100 m / min, spot diameter 2-5 mm, overlap rate 40-50%.
[0014] Furthermore, in step S2, the thickness of the cladding layer is 0.5-2.0 mm.
[0015] Furthermore, the wear-resistant coating is composed of the following components in parts by weight: 50-60 parts of epoxy resin, 25-50 parts of xylene, 15-25 parts of compound, 5-10 parts of curing agent, 0.1-0.3 parts of leveling agent, and 0.1-0.2 parts of defoaming agent.
[0016] Furthermore, the preparation method of the composite is as follows:
[0017] Mix tannic acid and deionized water evenly, add 4-formylphenylboronic acid and mix evenly, react for 2-4 hours, filter, and obtain a borate ester compound;
[0018] The aminated molybdenum disulfide, aminated silicon carbide and deionized water are uniformly mixed, a borate compound and acetic acid are added, and the mixture is reacted at 75-85° C. for 4-6 hours. After filtering, washing and drying, a composite is obtained.
[0019] In the above technical scheme, aldehyde groups are introduced by reacting tannic acid and 4-formylphenylboronic acid to obtain a borate ester compound; the amino molybdenum disulfide and the amino silicon carbide are evenly mixed, and the amino group and the aldehyde group on the borate ester compound undergo a Schiff base reaction to obtain a composite having good anti-wear and lubrication properties.
[0020] Furthermore, the mass ratio of the tannic acid, deionized water and 4-formylphenylboric acid is 1:(15-20):(0.5-1.0).
[0021] Furthermore, the composite is composed of the following components in parts by weight: 5-10 parts of amidated silicon carbide, 10-15 parts of amidated molybdenum disulfide, 15-25 parts of borate ester compound, 4-8 parts of acetic acid, and 50-70 parts of deionized water.
[0022] Furthermore, the preparation method of the amino-modified silicon carbide is as follows:
[0023] Step (1): 2,4,6-triaminopyrimidine and dimethyl sulfoxide are uniformly mixed, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane is added, and the mixture is reacted at 40-50° C. for 6-8 hours, and the mixture is distilled under reduced pressure to obtain modified pyrimidine;
[0024] Step (2): Silicon carbide, anhydrous ethanol, deionized water and modified pyrimidine are mixed evenly, reacted at 50-60° C. for 4-6 hours, filtered, washed and dried to obtain amino silicon carbide.
[0025] Furthermore, in the step (1), the mass ratio of 2,4,6-triaminopyrimidine, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane and dimethyl sulfoxide is 1:(2-3):(12-15).
[0026] Furthermore, in the step (2), the mass ratio of silicon carbide, anhydrous ethanol, deionized water and modified pyrimidine is 1:(15-20):(3-5):(2-4).
[0027] In the above technical scheme, the epoxy group at one end of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is used to undergo a ring-opening reaction with the amino group of 2,4,6-triaminopyrimidine, and then the other end of the silane is hydrolyzed to undergo a condensation reaction with the hydroxyl group on the surface of silicon carbide, thereby forming a chemical bond; at the same time, by adjusting the ratio of 2,4,6-triaminopyrimidine to 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the remaining amino group is retained on the surface of the amino silicon carbide, thereby obtaining amino silicon carbide.
[0028] Further, the preparation method of the amination molybdenum disulfide is as follows:
[0029] Step A: Under air conditions, maintaining molybdenum disulfide at 340-360° C. for 2-6 hours to obtain oxygen-etched molybdenum disulfide;
[0030] Step B: mixing oxygen-etched molybdenum disulfide, sodium hydroxide and deionized water uniformly, performing a hydrothermal reaction, centrifuging and separating, washing and drying to obtain pretreated molybdenum disulfide;
[0031] Step C: evenly mix the pretreated molybdenum disulfide and deionized water, add L-cysteine, perform ultrasonic treatment for 3-5 hours, continue stirring for 22-24 hours, and obtain amino molybdenum disulfide after filtering, washing and drying.
[0032] Furthermore, the mass ratio of oxygen-etched molybdenum disulfide, sodium hydroxide and deionized water is 1:(1-2):(50-60).
[0033] Furthermore, the process conditions of the hydrothermal reaction are: reacting at 200-220° C. for 6-8 hours.
[0034] Furthermore, the mass ratio of the pretreated molybdenum disulfide, L-cysteine and deionized water is 1:(1-2):(20-30).
[0035] In the above technical solution, molybdenum disulfide (MoS2 ) has a smooth surface and no active functional groups. 2 Oxygen etching in air followed by NaOH hydrothermal treatment yields MoS containing vacancies and defects. 2 , and then the sulfhydryl group on L-cysteine 2 The S vacancy is modified with amino to obtain amino molybdenum disulfide.
[0036] Furthermore, the concentration of the acetic acid is 0.1 mol / L.
[0037] Furthermore, the coating process conditions are: spraying method, spraying pressure 4-6MPa, spraying distance 230-250mm, moving speed 5-10m / min.
[0038] Furthermore, the wear-resistant coating has a thickness of 50-150 μm.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. A high wear-resistant piston rod based on a gas spring and a preparation method thereof of the present invention adopts a three-step method to prepare amino-modified molybdenum disulfide. First, MoS 2 Oxygen etching in air followed by NaOH hydrothermal treatment yields MoS containing vacancies and defects. 2 , and then the sulfhydryl group on L-cysteine 2 The S vacancies of MoS were modified with amino groups to successfully load L-cysteine onto the MoS 2 On, to obtain amination of molybdenum disulfide;
[0041] The epoxy group at one end of 3-(2,3-epoxypropoxy)propyltrimethoxysilane reacts with the amino group of 2,4,6-triaminopyrimidine to form a ring-opening reaction, and then the alkoxy group (-OCH 3 ) is hydrolyzed to form a chemical bond with silicon carbide, and the heterocyclic compound pyrimidine is introduced to increase the rigid structure, thereby improving the hardness of the material; at the same time, by adjusting the ratio of 2,4,6-triaminopyrimidine to 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, the remaining amino groups can be retained on the surface of the amino silicon carbide, thereby obtaining amino silicon carbide;
[0042] By reacting tannic acid and 4-formylphenylboronic acid, an aldehyde group is introduced to obtain a borate ester compound. During the friction process, the borate ester compound generates a composite film through a tribochemical reaction, which plays a role in reducing friction and resisting wear. Aminated molybdenum disulfide and aminated silicon carbide are evenly mixed, and the amino group and the aldehyde group on the borate ester compound undergo a Schiff base reaction to obtain a composite material, thereby achieving an effective combination of aminated molybdenum disulfide, aminated silicon carbide and borate ester compounds, and having the lubricating properties of molybdenum disulfide, the wear resistance of silicon carbide and the friction reducing effect of the borate ester compound, especially under high load and high friction conditions, thereby significantly improving the durability and service life of the piston rod.
[0043] 2. The present invention provides a high wear-resistant piston rod based on a gas spring and a preparation method thereof. The laser cladding process is used to prepare the cladding layer, which can form a uniform and dense coating and form a strong metallurgical bond with the substrate. The coating has excellent wear resistance and corrosion resistance. At the same time, the wear-resistant coating is applied to further enhance the surface hardness and wear resistance of the coating, so that the piston rod can effectively prevent wear in a high friction environment. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In this embodiment, the iron-based alloy powder: brand Fe50, particle size is 45μm, sourced from Nangong Xindun Alloy Welding Material Spraying Co., Ltd.; molybdenum disulfide: particle size is 1250 mesh, sourced from Jinan Ruixin Chemical Co., Ltd.; silicon carbide: particle size is 500 mesh, sourced from Zhengzhou Xinli Wear-resistant Materials Co., Ltd.; leveling agent: brand is Keying KYC-615; defoaming agent: brand is BYK-028; curing agent: polyamide 650, sourced from Jinan Langsheng New Materials Co., Ltd.; piston rod: material 316L stainless steel, sourced from Wuxi Jingheng Hydraulic Components Co., Ltd.
[0046] In the following examples and comparative examples, 1 part is equal to 10 g.
[0047] Embodiment 1: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0048] Step S1: Degreasing, cleaning and drying the piston rod to obtain a pre-treated piston rod;
[0049] Step S2: cladding the iron-based alloy powder on the surface of the pretreated piston rod by laser cladding process (laser power 3500 W, cladding speed 10 m / min, spot diameter 2 mm, overlap rate 40%) to form a cladding layer;
[0050] Step S3: 50 parts of epoxy resin and 25 parts of xylene are mixed evenly, and 15 parts of the composite, 5 parts of the curing agent, 0.1 parts of the leveling agent and 0.1 parts of the defoaming agent are added and mixed evenly to obtain a wear-resistant coating;
[0051] Step S4: coating the cladding layer with a wear-resistant coating (by spraying, with a spraying pressure of 4 MPa, a spraying distance of 230 mm, and a moving speed of 5 m / min), and after drying and curing, forming a wear-resistant coating to obtain a high-wear-resistant piston rod;
[0052] The preparation method of the complex is as follows:
[0053] 20 parts of tannic acid and 300 parts of deionized water were mixed evenly, 10 parts of 4-formylphenylboric acid were added and mixed evenly, reacted for 2 hours, filtered, and a borate ester compound was obtained;
[0054] 5 parts of amidated silicon carbide, 10 parts of amidated molybdenum disulfide and 50 parts of deionized water were mixed evenly, 15 parts of borate compound and 4 parts of 0.1 mol / L acetic acid were added, reacted at 75°C for 4 hours, filtered, washed and dried to obtain a composite;
[0055] The preparation method of amination silicon carbide is as follows:
[0056] Step (1): 10 parts of 2,4,6-triaminopyrimidine and 120 parts of dimethyl sulfoxide are mixed evenly, 20 parts of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane are added, and the mixture is reacted at 40° C. for 6 hours, and the mixture is distilled under reduced pressure to obtain modified pyrimidine;
[0057] Step (2): 5 parts of silicon carbide, 75 parts of anhydrous ethanol, 15 parts of deionized water and 10 parts of modified pyrimidine are mixed evenly, reacted at 50° C. for 4 hours, filtered, washed and dried to obtain amino silicon carbide;
[0058] The preparation method of amination molybdenum disulfide is as follows:
[0059] Step A: Under air conditions, 10 parts of molybdenum disulfide are placed in a tube furnace and maintained at 340° C. for 6 hours to obtain oxygen-etched molybdenum disulfide;
[0060] Step B: 10 parts of oxygen-etched molybdenum disulfide, 10 parts of sodium hydroxide and 500 parts of deionized water are mixed evenly, poured into a polytetrafluoroethylene-lined high-pressure reactor, reacted at 200° C. for 6 hours, centrifuged, washed and dried to obtain pretreated molybdenum disulfide;
[0061] Step C: 10 parts of pretreated molybdenum disulfide and 200 parts of deionized water are mixed evenly, 10 parts of L-cysteine are added, ultrasonic treatment is performed for 3 hours, stirring is continued for 22 hours, and after filtering, washing and drying, amino molybdenum disulfide is obtained.
[0062] Embodiment 2: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0063] Step S1: Degreasing, cleaning and drying the piston rod to obtain a pre-treated piston rod;
[0064] Step S2: cladding the iron-based alloy powder on the surface of the pretreated piston rod by laser cladding process (laser power 4000 W, cladding speed 50 m / min, spot diameter 3 mm, overlap rate 45%) to form a cladding layer;
[0065] Step S3: 55 parts of epoxy resin and 40 parts of xylene are mixed evenly, and 20 parts of the composite, 8 parts of the curing agent, 0.2 parts of the leveling agent and 0.15 parts of the defoaming agent are added and mixed evenly to obtain a wear-resistant coating;
[0066] Step S4: coating the cladding layer with a wear-resistant coating (by spraying, with a spraying pressure of 5 MPa, a spraying distance of 240 mm, and a moving speed of 9 m / min), and after drying and curing, forming a wear-resistant coating to obtain a high-wear-resistant piston rod;
[0067] The preparation method of the complex is as follows:
[0068] 20 parts of tannic acid and 360 parts of deionized water were mixed evenly, 16 parts of 4-formylphenylboric acid were added and mixed evenly, reacted for 3 hours, filtered, and a borate ester compound was obtained;
[0069] 8 parts of amidated silicon carbide, 12 parts of amidated molybdenum disulfide and 60 parts of deionized water were mixed evenly, 20 parts of borate ester compound and 6 parts of 0.1 mol / L acetic acid were added, reacted at 80°C for 5 hours, filtered, washed and dried to obtain a composite;
[0070] The preparation method of amination silicon carbide is as follows:
[0071] Step (1): 24 parts of 2,4,6-triaminopyrimidine and 312 parts of dimethyl sulfoxide were mixed evenly, 60 parts of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane were added, and the mixture was reacted at 45° C. for 7 hours, and the mixture was distilled under reduced pressure to obtain modified pyrimidine;
[0072] Step (2): 8 parts of silicon carbide, 144 parts of anhydrous ethanol, 32 parts of deionized water and 24 parts of modified pyrimidine are mixed evenly, reacted at 55° C. for 5 hours, filtered, washed and dried to obtain amino silicon carbide;
[0073] The preparation method of amination molybdenum disulfide is as follows:
[0074] Step A: Under air conditions, 12 parts of molybdenum disulfide are placed in a tube furnace and maintained at 350° C. for 4 hours to obtain oxygen-etched molybdenum disulfide;
[0075] Step B: 12 parts of oxygen-etched molybdenum disulfide, 18 parts of sodium hydroxide and 660 parts of deionized water are mixed evenly, poured into a polytetrafluoroethylene-lined high-pressure reactor, reacted at 210° C. for 7 hours, centrifuged, washed and dried to obtain pretreated molybdenum disulfide;
[0076] Step C: 12 parts of pretreated molybdenum disulfide and 300 parts of deionized water are mixed evenly, 18 parts of L-cysteine are added, ultrasonic treatment is performed for 4 hours, stirring is continued for 23 hours, and after filtering, washing and drying, amino molybdenum disulfide is obtained.
[0077] Embodiment 3: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0078] Step S1: Degreasing, cleaning and drying the piston rod to obtain a pre-treated piston rod;
[0079] Step S2: cladding the iron-based alloy powder on the surface of the pretreated piston rod by laser cladding process (laser power 4500 W, cladding speed 100 m / min, spot diameter 5 mm, overlap rate 50%) to form a cladding layer;
[0080] Step S3: 60 parts of epoxy resin and 50 parts of xylene are mixed evenly, and 25 parts of the composite, 10 parts of the curing agent, 0.3 parts of the leveling agent and 0.2 parts of the defoaming agent are added and mixed evenly to obtain a wear-resistant coating;
[0081] Step S4: coating the cladding layer with a wear-resistant coating (by spraying, with a spraying pressure of 6 MPa, a spraying distance of 250 mm, and a moving speed of 10 m / min), and after drying and curing, forming a wear-resistant coating to obtain a high-wear-resistant piston rod;
[0082] The preparation method of the complex is as follows:
[0083] 20 parts of tannic acid and 400 parts of deionized water were mixed evenly, 20 parts of 4-formylphenylboric acid were added and mixed evenly, reacted for 4 hours, filtered, and a borate ester compound was obtained;
[0084] 10 parts of amidated silicon carbide, 15 parts of amidated molybdenum disulfide and 70 parts of deionized water were mixed evenly, 25 parts of borate ester compound and 8 parts of 0.1 mol / L acetic acid were added, reacted at 85°C for 6 hours, filtered, washed and dried to obtain a composite;
[0085] The preparation method of amination silicon carbide is as follows:
[0086] Step (1): 2,4,6-triaminopyrimidine and dimethyl sulfoxide are uniformly mixed, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane is added, and the mixture is reacted at 40-50° C. for 6-8 hours, and the mixture is distilled under reduced pressure to obtain modified pyrimidine;
[0087] Step (2): mixing silicon carbide, anhydrous ethanol, deionized water and modified pyrimidine uniformly, reacting at 60° C. for 6 hours, filtering, washing and drying to obtain amino silicon carbide;
[0088] The preparation method of amination molybdenum disulfide is as follows:
[0089] Step A: Under air conditions, 15 parts of molybdenum disulfide are placed in a tube furnace and maintained at 360° C. for 2 hours to obtain oxygen-etched molybdenum disulfide;
[0090] Step B: 15 parts of oxygen-etched molybdenum disulfide, 30 parts of sodium hydroxide and 900 parts of deionized water are mixed evenly, poured into a polytetrafluoroethylene-lined high-pressure reactor, reacted at 220° C. for 8 hours, centrifuged, washed and dried to obtain pretreated molybdenum disulfide;
[0091] Step C: 15 parts of pretreated molybdenum disulfide and 450 parts of deionized water are mixed evenly, 30 parts of L-cysteine are added, ultrasonic treatment is performed for 5 hours, stirring is continued for 24 hours, and after filtering, washing and drying, amino molybdenum disulfide is obtained.
[0092] Comparative Example 1: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0093] Compared with Example 2, the composite of Comparative Example 1 does not contain aminated molybdenum disulfide, and the other steps are the same as those of Example 2.
[0094] Comparative Example 2: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0095] Compared with Example 2, Comparative Example 2 replaces the amino-treated silicon carbide with silicon carbide of the same mass, and the other steps are the same as those of Example 2.
[0096] Comparative Example 3: A method for preparing a highly wear-resistant piston rod based on a gas spring, comprising the following processes:
[0097] The preparation method of amination silicon carbide is as follows:
[0098] Step (1): 24 parts of 2,4,6-triaminopyrimidine and 312 parts of dimethyl sulfoxide were mixed evenly, 144 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane were added, and the mixture was reacted at 45° C. for 7 hours, and the mixture was distilled under reduced pressure to obtain modified pyrimidine;
[0099] Step (2): 8 parts of silicon carbide, 144 parts of anhydrous ethanol, 32 parts of deionized water and 24 parts of modified pyrimidine are mixed evenly, reacted at 55° C. for 5 hours, filtered, washed and dried to obtain amino silicon carbide;
[0100] Compared with Example 2, in step (1) of Comparative Example 3, the mass ratio of 2,4,6-triaminopyrimidine to 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1:6, and the other steps are the same as Example 2.
[0101] Experiment: Take the high wear-resistant piston rods obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, test their performances respectively and record the test results:
[0102] Microhardness test: Use HXD-1000TMC metallographic microhardness tester, place the sample on the microhardness tester, set the load pressure P of the hardness tester to 20N, and maintain the pressure for 15s to make an indentation, calculate the Vickers hardness of the composite coating, take an average of 10 points on the cross section of the sample coating, and take the arithmetic mean of the final result of the coating hardness.
[0103] Wear resistance test: The friction coefficient of the sample was measured using a sliding friction and wear tester (RtecMFT-3000) to simulate the wear of the piston rod in actual work. The test parameters were set as follows: normal load 50N, displacement amplitude 4.5mm, wear time 1800s, room temperature, and the wear piece was a GCr15 steel ball. After the test, the wear scar morphology of the coating was observed, and the wear volume was measured using a white light interferometer (Usp-Sigma).
[0104] The test results are as follows:
[0105] Microhardness / HV <![CDATA[Wear volume / mm 3 > Friction coefficient Example 1 924 4.3 0.18 Example 2 932 4.0 0.16 Example 3 928 4.2 0.20 Comparative Example 1 889 5.2 0.32 Comparative Example 2 906 4.8 0.28 Comparative Example 3 915 4.6 0.25
[0106] According to the data in the above table, we can clearly draw the following conclusions:
[0107] 1. Compared with Examples 1-3, the microhardness of the products obtained in Comparative Examples 1 and 2 decreased, and the wear volume and friction coefficient increased, indicating that the composite prepared by adding amino molybdenum disulfide in the present invention has better lubrication performance, thereby effectively improving the wear resistance of the material; compared with unmodified silicon carbide, the amino silicon carbide prepared by the present invention has better reaction activity and introduces a rigid pyrimidine structure, thereby improving the wear resistance of the coating.
[0108] 2. Compared with Examples 1-3, the microhardness of the product obtained in Comparative Example 3 decreases, while the wear volume and friction coefficient increase. It can be seen that when an excessive amount of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added, the amino group will completely react, thereby affecting the subsequent reaction. Therefore, the performance of the amino silicon carbide prepared by the present invention is affected by the ratio of each reagent in its preparation process. By selecting the mass ratio within the range, amino silicon carbide with excellent wear resistance can be obtained.
[0109] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a highly wear-resistant piston rod based on a gas spring, characterized in that: The steps include: Step S1: Degreasing, cleaning and drying the piston rod to obtain a pre-treated piston rod; Step S2: cladding the cladding powder onto the surface of the pretreated piston rod through a laser cladding process to form a cladding layer; Step S3: mixing epoxy resin and xylene evenly, adding the composite, curing agent, leveling agent and defoaming agent and mixing evenly to obtain a wear-resistant coating; Step S4: coating the surface of the cladding layer with a wear-resistant coating, and forming a wear-resistant coating after drying and curing to obtain a highly wear-resistant piston rod.
2. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 1, characterized in that: In the step S2, the cladding powder is iron-based alloy powder.
3. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 1, characterized in that: In step S2, the laser cladding process conditions are: laser power 3500-4500W, cladding speed 10-100m / min, spot diameter 2-5mm, overlap rate 40-50%.
4. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 1, characterized in that: The wear-resistant coating is composed of the following components in parts by weight: 50-60 parts of epoxy resin, 25-50 parts of xylene, 15-25 parts of compound, 5-10 parts of curing agent, 0.1-0.3 parts of leveling agent and 0.1-0.2 parts of defoaming agent.
5. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 4, characterized in that: The preparation method of the composite is as follows: Mix tannic acid and deionized water evenly, add 4-formylphenylboronic acid and mix evenly, react for 2-4 hours, filter, and obtain a borate ester compound; The aminated molybdenum disulfide, aminated silicon carbide and deionized water are uniformly mixed, a borate compound and acetic acid are added, and the mixture is reacted at 75-85° C. for 4-6 hours. After filtering, washing and drying, a composite is obtained.
6. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 5, characterized in that: The mass ratio of the tannic acid, deionized water and 4-formylphenylboric acid is 1:(15-20):(0.5-1.0).
7. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 5, characterized in that: The composite is composed of the following components in parts by weight: 5-10 parts of amidated silicon carbide, 10-15 parts of amidated molybdenum disulfide, 15-25 parts of borate ester compound, 4-8 parts of acetic acid, and 50-70 parts of deionized water.
8. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 7, characterized in that: The preparation method of the amino silicon carbide is as follows: Step (1): 2,4,6-triaminopyrimidine and dimethyl sulfoxide are uniformly mixed, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane is added, and the mixture is reacted at 40-50° C. for 6-8 hours, and the mixture is distilled under reduced pressure to obtain modified pyrimidine; Step (2): Silicon carbide, anhydrous ethanol, deionized water and modified pyrimidine are mixed evenly, reacted at 50-60° C. for 4-6 hours, filtered, washed and dried to obtain amino silicon carbide.
9. The method for preparing a highly wear-resistant piston rod based on a gas spring according to claim 7, characterized in that: The preparation method of the amination molybdenum disulfide is as follows: Step A: Under air conditions, maintaining molybdenum disulfide at 340-360° C. for 2-6 hours to obtain oxygen-etched molybdenum disulfide; Step B: mixing oxygen-etched molybdenum disulfide, sodium hydroxide and deionized water uniformly, performing a hydrothermal reaction, centrifuging and separating, washing and drying to obtain pretreated molybdenum disulfide; Step C: The pretreated molybdenum disulfide and deionized water are mixed evenly, L-cysteine is added, ultrasonic treatment is performed for 3-5 hours, stirring is continued for 22-24 hours, and after filtering, washing and drying, amino molybdenum disulfide is obtained.
10. A highly wear-resistant piston rod based on a gas spring prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Wear and corrosion resistant nickel-based SiC composite coating for marine hydraulic piston rod and preparation method thereof
CN109628927A
Enhanced self-lubricating joint bearing gasket material preparation method
CN110564289A
Method for repairing and remanufacturing surface of piston rod
CN114150255A
Wear-resistant and corrosion-resistant coating on surface of piston rod and preparation method thereof
CN115161637A
Ultrahigh corrosion-resistant and wear-resistant composite coating on surface of piston rod and preparation method
CN115747800A